POTRET REMAJA BERPERILAKU MENYIMPANG DI KECAMATAN MANDAU KABUPATEN BENGKALIS DURI - Siswanto Purba; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This thesis is submitted in order to qualify holds a Bachelor of Sociology. With the title " The Teen Portrait of Behave Deviating in Mandau District Of Gutter Village Duri Bengkalis. The issues discussed in this paper is to describe the factors adolescents do deviant behavior and characteristics of adolescents who commit deviant behavior. The issue of juvenile crime should receive special attention from both families especially those of the parents who are the closest to the teens. Teen issues have become a social reality in our society, especially when taken into consideration that the teen generation is going to fill a variety of positions in society in the future that will continue the life of society, the nation and the State in the future. The subject of this research were all adolescents who do meyimpang behavior. The sampling technique used in this research is census techniques. Census technique is a method of sampling as a whole. The method used is quantitative descriptive method with quantitative and qualitative data analysis. Data screening instruments are observation, questionnaires, and documents. The theory is used to issue the factors of deviant behavior is by EH Sutherland who say evil person behaves the same way with the evil behavior. That is, evil behavior is studied in interaction with others and the person is getting nasty behavior as a result of interactions made by people who behave in a tendency against the norms of existing laws. Further Sutherland called it a differential association process (differential association), because what is learned in the process, as a result of interaction with the patterns of malicious behavior. The theory is also used Kartini theory subculture theory linking Kartono about trust or confidence, certain ambitions (eg its ambitions material, relaxed life, a criminal pattern, heterosexual relationships are free, and others) that motivate the emergence of groups of teenagers brandalan and criminal.Results of research in general is done then the writer can say that meyimpang behavioral factors that most affect young people do is a playmate and economic factors , playmates became one of the factors that influence as a teenage friends playing a social action in the achievement of the character himself . Economic factors are sufficient to support the juvenile perform deviant behavior , adolescents with live well is not always avoid deviant acts , live with all the facilities that are already available causes teens to feel bored and looking for something that they do not get at home . Beyond the search process is not always a positive value but often teenagers confronted with the values that are negative.Keywords : Juvenile Delinquency , Deviant Behavior